The Constitutional Context of Computing in Portugal - Article 35 - Pedro Ramos Brandao (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
the creation and evolution of Article 35 of the Portuguese Republic's Constitution. The ordinary legislation related to article 35. European legislation related to the protection of personal data. The General Regulation of Data Protection.